La autoincriminación en la conciliación y en el procedimiento abreviado en la legislacion Ecuatoriana - Zúñiga Molina, Estevan Ismael (2018)
This research work entitled: The study of criminal procedures, the same ones that violate the rights of Ecuadorians, by the fact that the accused person must self-incriminate or declare against the responsibility for a contravention or crime that has been consummated. These procedures are the following: The first is basically framed in traffic infractions whose final result is not death, the law provides for judicial processes as extrajudicial based on conciliatory agreements with the main objective of giving a brief processing to these conflicts, so that in a procedure of this characteristic it is possible to reach conciliation, it must first go through an element, which is prescribed by Article 7 of Resolution 327-2014 issued by the Plenary of the Judicial Council, in which it says that it can just be a conciliatory agreement, which is due to the fact that there can only be a conciliatory agreement when, in a mandatory way, there is a declaration of responsibility of one of the parties involved in the conflict, which leads to think of the violation of the right not to incriminate oneself. The second procedure of this investigation is framed in articles 635 to 639 of the Integral Organic Penal Code, as an annex to the manual. In this procedure, like the previous one, the person prosecuted must declare his guilt to be able to access certain legal benefits, such as negotiating the penalty after fulfilling several requirements that the law stipulates; being the legislator who has identified this procedure with the aim of achieving a much shorter judicial process. Based on the facts, the constitutionality will be studied, legality as the procedure in reference to the right of not self-incrimination enshrined in the Constitution of the Republic of Ecuador, in article 77 numeral 7 literal c.